2008
DOI: 10.1111/j.1467-8489.2008.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Demand for fish in Asia: a cross‐country analysis*

Abstract: Fish demand patterns in nine Asian countries were investigated using a multistage budgeting framework allowing a disaggregated approach to analysing fish consumption. This paper highlights the heterogeneity of fisheries products in terms of species, sources and cultural responses of consumers, factors that are important in fish demand under the Asian setting. Specifically, fish demand by income groups were compared to determine how the low-and high-income households respond to price and income changes. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 25 publications
(22 reference statements)
3
53
0
3
Order By: Relevance
“…This statement is supported with the results of some studies suggested a negative relationship between supply of fish and market price (Hasan and Middendorp 1999;Briones et al 2004;Burger et al 2004;Dey et al 2008). According to Dey (2000), increased supply of tilapia will reduce market prices by 5-16% in Bangladesh.…”
Section: Factors Affecting Price Of Tilapiasupporting
confidence: 79%
“…This statement is supported with the results of some studies suggested a negative relationship between supply of fish and market price (Hasan and Middendorp 1999;Briones et al 2004;Burger et al 2004;Dey et al 2008). According to Dey (2000), increased supply of tilapia will reduce market prices by 5-16% in Bangladesh.…”
Section: Factors Affecting Price Of Tilapiasupporting
confidence: 79%
“…Seafood is also a preferred and culturally important food choice in ASEAN region [51] ( Dey et al 2008). Production and consumption of meat and fish have serious consequences for global food security and the environment [52,53,54].…”
Section: Implications To Food and Nutritional Securitymentioning
confidence: 99%
“…Over the long term, the misrepresentation of the quality and safety of farmed Asian fish puts the EU in a precarious position with respect to securing adequate fish supplies. The highly income elastic character of fish [47] implies that as Asian, and other developing country, economies grow, so will demand for seafood. The rise of an Asian middle class, with an almost insatiable appetite for not only more but higher quality and added value seafood [48] means that Europe will face increasingly greater competition for a share of global fish trade.…”
Section: 'New' Food Ethics and The Turning Tide Of Fish Tradementioning
confidence: 99%